Addressing gaps in surgical skills training by means of low-cost simulation at Muhimbili University in Tanzania - Taché Stephanie; Mbembati Naboth; Marshall Nell; Tendick Frank; Mkony Charles; O'Sullivan Patricia (BMC, 2009)
Abstract Background Providing basic surgical and emergency care in rural settings is essential, particularly in Tanzania, where the mortality burden addressable by emergency and surgical interventions has been estimated at 40%. However, the shortages of teaching faculty and insufficient learning resources have hampered the traditionally intensive surgical training apprenticeships. The Muhimbili University of Health and Allied Sciences consequently has experienced suboptimal preparation for graduates practising surgery in the field and a drop in medical graduates willing to become surgeons. To address the decline in circumstances, the first step was to enhance technical skills in general surgery and emergency procedures for senior medical students by designing and implementing a surgical skills practicum using locally developed simulation models. Methods A two-day training course in nine different emergency procedures and surgical skills based on the Canadian Network for International Surgery curriculum was developed. Simulation models for the surgical skills were created with locally available materials. The curriculum was pilot-tested with a cohort of 60 senior medical students who had completed their surgery rotation at Muhimbili University. Two measures were used to evaluate surgical skill performance: Objective Structured Clinical Examinations and surveys of self-perceived performance administered pre- and post-training. Results Thirty-six students participated in the study. Prior to the training, no student was able to correctly perform a surgical hand tie, only one student was able to correctly perform adult intubation and three students were able to correctly scrub, gown and glove. Performance improved after training, demonstrated by Objective Structured Clinical Examination scores that rose from 6/30 to 15/30. Students perceived great benefit from practical skills training. The cost of the training using low-tech simulation was four United States dollars per student. Conclusion Simulation is valued to gain experience in practising surgical skills prior to working with patients. In the context of resource-limited settings, an additional benefit is that of learning skills not otherwise obtainable. Further testing of this approach will determine its applicability to other resource-limited settings seeking to develop skill-based surgical and emergency procedure apprenticeships. Additionally, skill sustainability and readiness for actual surgical and emergency experiences need to be assessed.